Cerebral Venous Sinus Thrombosis in 2 Children With Celiac Disease - CESUR, YAŞAR; Dogan, Murat; Peker, Erdal; Akbayram, Sinan; Bektas, Mehmet S.; Başaranoğlu, Murat; Cesur, YAŞAR; Caksen, Huseyin (My University, 2011)
Cerebral venous sinus thrombosis (CVST) is an uncommon disease in childhood. In the largest study carried out so far, the incidence was 0.67 case per 100 000 children per year. A number of etiologies and risk factors have been so far identified for CVST in childhood, including head trauma, local and systemic infectious diseases, malignancies, and autoimmune diseases. Celiac disease (CD) is a disease of the small intestine caused by an immune response to ingested gluten. Epilepsy, bilateral occipital calcification, cerebellar ataxia, degenerative central nervous system disease, peripheric neuropathy, myopathy, and rarely stroke were defined as neurologic disorders. In this presentation, we report 2 cases (16-year-old boy and 2-year-old boy) with CD and CVST. We emphasized that CD can be investigated in patients with CVST even with the absence of gastrointestinal symptoms. Finally, we suggest that algorithm of CVST can be involved in the investigation of CD.